The lipid peroxidation of isolated goatfetuses with umbilical arterio-venous extracorporeal membrane oxigenation - RYO Eiji; UNNO Nohuya; OKAI Takashi; TAKETANI Yuji; KUWABARA Yoshinori (Jinko Zoki, 1993)
Oxygen-derived free radicals have been interested as mediators of the injury during exnacorporeal membrane oxygenalion. Feluses live in hypoxic conditions and it is getting clear that they are sensitive to free radicals. We investigated lipid pet oxidations in the blood of goat letuses, adult goats, and isolated goat fetuses with umbilical arterio-venous exlracorporcal membrane oxygenation (ECMO) by the Yagi' method. Resalts were as follows, the blood lipid peroxidations of goal fetuses; 2.1±0.6nmol/ml (mean±S. D., N=10), adult goals; 1.5±0.4nmol/ml (N=48), fetuses with ECMO (of 50-70 hours incuhatiun time, cardiovascular states have been stable in this period): 3.0±1.3nmol/ml (N=10), and especially, those of fetuses wilh less than 120 days of age with ECMO: 4.0±0.8nmol/ml (N=3). It was suggested that free radical injury existed in this experimental system, especially in the cases of immature fetuses. 体外循環に伴う組織障害の原因の一つにブリーラジカル障害が注目されているが、生理的に低酸素状態にあり、ブリーラジカル障害に抵抗性の弱いヤギ胎仔を用いた人工肺による子宮外保育実験でそれを検討した, フリーラジカル隆害の指標として体外循環血の血漿過酸化脂質値を八木法にて測定した。また、通常の胎仔臍帯血及び、回路のプライミングと保育中の輸血に川いる成獣血の血漿過酸化脂質値も測定、検討した。それぞれ血漿過酸化脂質値は)胎仔臍帯血:2.1±0.6nmol/ml (N=13)、成獣血:1.5±0,4nmoi/ml (N=48)、体外循環血(子宮外保育50～70時間):3.0±1.3nmol/ml (N=10)、特に120 II未満の胎仔での体外循環では4.0.±0.8nmol//ml (N=3)と高値であり、ブリーラジカル障害の存在が示唆された,